The Role of Hedonic Consumption Tendency and Positive Emotion in Mediating the Influence of Fashion Involvement on Impulsive Buying - Satria, Sandi; Kaihatu, Thomas Stefanus (Review of Management and Entrepreneurship, 2022)
Fashion products are one of the most popular types of products and are often purchased by people in general especially in Indonesia. Many individuals are willing to spend a lot of time just to improve the appearance in order to be able to follow the fashion trends that occur at certain time. This thing that becomes the reason why many consumers often make un- planned purchase of fashion products or in other words do impulsive buy- ing. This research is done to find out the contribution of fashion involve- ment, hedonic consumption tendency, and positive emotion on impulsive buying, then the contribution of fashion involvement on hedonic consump- tion tendency and positive emotion, and the effect of hedonic consump- tion tendency and positive emotion in mediating the influence of fashion involvement on impulsive buying. Data collection in this research is done by distributing 120 questionnaire method using Google form to the cus- tomers who have ever purchased fashion products at Beachwalk Bali mall. In this research, sampling is done with purposive sampling method. The questionnaires that are feasible to be analyzed are 97 questionnaires. The results of this research indicate that (1) fashion involvement, hedonic con- sumption tendency, and positive emotion affect positive and significant on impulsive buying, (2) fashion involvement affects positive and significant on hedonic consumption tendency and positive emotion, and (3) hedonic consumption tendency. and positive emotion partially mediate the relation between fashion involvement on impulsive buying. Keywords: fashion; fashion involvement; hedonic consumption tendency; positive emotion; impulsive buying